Spirochaetes as a cause of intense plasmacytic inflammation. Issue 10 (October 2017) - Rees, Gabrielle G.; Mucklow, Stuart; Royston, Daniel J.; Soilleux, Elizabeth J.
Abstract: A 51-year-old man was referred with clinically suspected tonsillar malignancy. Biopsy showed dense plasmacytic inflammation, comprising polytypic plasma cells. Immunostaining for spirochaetes was positive and the diagnosis of syphilis was subsequently confirmed on serology. The differential diagnoses of intense plasmacytic inflammation include lymphoplasmacytic malignancy (with predominantly plasmacytic differentiation), plasmacytoma/multiple myeloma, IgG4-related disease and syphilis. Syphilis can be diagnosed on histological sections using silver stains or anti-spirochaete immunohistochemistry.